Simultaneous Determination of Four Ingredients in Plantago Depressa by Single Marker. (21st December 2021) - Xu, Yang; Wang, Yuejie; Bi, Shengnan; Jia, Yanxue; Bao, Huiwei
Abstract : Objective . To establish a quantitative analysis of multicomponents by single marker (QAMS) method for the simultaneous determination of 4 active components such as protocatechuic acid, catechin, quercetin, and luteolin in Plantago depressa . Method . 4 active components in Plantago depressa were studied. Quercetin was used as an internal reference to establish the relative correction factors among protocatechuic acid, catechin, and luteolin and calculate the contents of each component; the results were compared with those measured by the external standard method. Results . 4 components showed a good linear relationship in their respective concentration ranges ( r  > 0.9995). The relative correction factors (fs/k) of protocatechuic acid, catechin, and luteolin were 1.1992, 0.8613, and 1.6069, respectively. The method had good durability. The contents of protocatechuic acid, catechin, and luteolin calculated by QAMS were not significantly different from those measured by the external standard method. Conclusion . QAMS can be used to determine the content of 4 components in Plantago depressa at the same time, and the method is simple, accurate, and can be used for quality control.